Diseño y construcción de un sistema de clasificación de granulado de panela mediante un modelo tipo zaranda. - Arias Cordero, Jhon Ernesto (2012)
In short, within the research process of this project was undertaken to design a sorting machine granules to obtain granulated brown sugar, thus providing an optimal solution for the company "OCAMPOS". Through various studies it has been determined that the panela agroindustry Ecuador has important roles in economic, social, food security, cultural and environmental. These elements highlight panela agroindustry as a key production strategy in reducing poverty, as favoring sustainable access to natural resources increases the local and regional capital and contributes to the diversification of income of peasant producers. The sorter Zaranda granulated panela, is designed to perform the classification of 1.5 tons per hour of work, or 60 quintals per day since the machine work 4 hours a day. Measurements of the sieve box are 1 meter long, 0.45 meters wide and 0.6 meters high since it consists of two sieves of different diameter holes, spaced 20 cm apart. The system of vibration of the housing is produced by an eccentric mass outdated shaft rotating at 2350 rev / min. This axis was calculated taking into account security settings, working with high quality material such as steel and AISI 4140. The fundamental purpose of designing and building a machine that has the ability to sort the granulated brown sugar, in addition to this the machine would have to be easy to use and maintenance and the ability to meet the demand of production, another important aspect was to select materials for constructing the machine, these materials also were chosen to meet the mechanical requirements of design are readily available and relatively inexpensive. In order to validate the proposed alternative has built a shaker type sorting machine, this construct was made following the due process, which first began with a detailed design of all components of the machine. The element is in more detail the design was as shaft due to the unbalanced mass (eccentric) is subjected to various stresses, so it was possible to check topics such as yield strength, resistance to limit fatigue factors shock, shear, bending moment these among the main. Finally the calculated diameter for shaft was 1 1/4 inch, using as material for the construction of this, the AISI 4140 steel.